2013
DOI: 10.1099/mic.0.064865-0
|View full text |Cite
|
Sign up to set email alerts
|

Central metabolism controls transcription of a virulence gene regulator in Vibrio cholerae

Abstract: ToxT is the central regulatory protein involved in activation of the main virulence genes in Vibrio cholerae. We have identified transposon insertions in central metabolism genes, whose disruption increases toxT transcription. These disrupted genes encode the primary respiration-linked sodium pump (NADH : ubiquinone oxidoreductase or NQR) and certain tricarboxylic acid (TCA) cycle enzymes. Observations made following stimulation of respiration in the nqr mutant or chemical inhibition of NQR activity in the TCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 53 publications
5
45
0
Order By: Relevance
“…We had previously suggested that TCA cycle activity is decreased in the V. cholerae Δ nqrA-F mutant [10]. Consistent with this, intracellular isocitrate levels were decreased in the Δ nqrA-F mutant (Table 3).…”
Section: Resultssupporting
confidence: 75%
“…We had previously suggested that TCA cycle activity is decreased in the V. cholerae Δ nqrA-F mutant [10]. Consistent with this, intracellular isocitrate levels were decreased in the Δ nqrA-F mutant (Table 3).…”
Section: Resultssupporting
confidence: 75%
“…However, FadR clearly regulates the expression of additional genes in V. cholerae and one or more of these may influence the transcription of toxT. Since the toxT promoter is responsive to changes in central metabolism (58), it is also possible that global metabolic changes that occur in the ΔfadR mutant result in altered transcription of ToxT.…”
Section: Discussionmentioning
confidence: 99%
“…ions are accumulated inside the cell and electrochemical ion gradient may be enforced to shift and subsequently reduce the virulence and motility of V. cholerae. Accumulation of oxaloacetate itself could result in virulence suppression because this has been reported to inhibit the expression of ToxT, a global regulator of virulence in V. cholerae [39].…”
Section: Effect Of Indole On V Cholerae Virulencementioning
confidence: 99%